Mesocosm experiment on the influence of heatwave on plankton - Cédric Léo Meunier (PANGAEA, 2025)
In the context of global change, marine organisms are subjected not only to gradual changes in abiotic parameters, but also to an increasing number of extreme events, such as heatwaves. However, we still know little about the influence of heatwaves on the structure of marine communities, and experimental studies are needed to test the impact of heatwaves alone, and in combination with other environmental drivers. Here, we conducted a mesocosm experiment and applied an integrated multiple driver design to assess the potential impact of heatwaves under ambient and future environmental conditions on natural coastal plankton communities. To represent future environmental conditions, temperature and pH were manipulated based on the Representative Concentration Pathway 8.5 proposed by the IPCC for 2100, and dissolved N:P ratios were increased to simulate the conditions expected in European coastal zones. Throughout the experiment, we measured abiotic conditions as well as the abundance of bacterioplankton, phytoplankton, and microzooplankton.